2004
DOI: 10.1007/s10350-004-0608-x
|View full text |Cite
|
Sign up to set email alerts
|

Flat Lesions of the Colorectal Mucosa: Differences in Recognition Between Japanese and American Endoscopists

Abstract: There are significant differences in interpretation of the shape of lesions of the colorectal mucosa between Japanese colonoscopists and their American counterparts. These differences are likely to account for some of the apparent differences in incidence in series of flat colorectal adenomas reported from Japan and Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
(13 reference statements)
3
16
0
Order By: Relevance
“…The prevalence of neoplasia was 45.7 and 34.9% in patients who were screened by the self-trained and control colonoscopists in our VA average risk colon cancer screening population, respectively. Our findings provide validation in a live endoscopy clinical setting to the report by Church and colleagues who showed that American colonoscopists may under-diagnose NP-CRN [18]. NP-CRNs, however, only contributed to approximately one-third of the additional neoplasia detected.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of neoplasia was 45.7 and 34.9% in patients who were screened by the self-trained and control colonoscopists in our VA average risk colon cancer screening population, respectively. Our findings provide validation in a live endoscopy clinical setting to the report by Church and colleagues who showed that American colonoscopists may under-diagnose NP-CRN [18]. NP-CRNs, however, only contributed to approximately one-third of the additional neoplasia detected.…”
Section: Discussionsupporting
confidence: 83%
“…One of the major differences between American and Japanese endoscopists in a recently reported comparative study of polyp recognition was that Americans thought that an average of 9 percent of flat diminutive lesions were variants of normal, whereas this did not happen at all with the Japanese colonoscopists. 21 Thus, colonoscopists may see an adenoma but may not recognize it as abnormal. Similarly, adenomas may be mistaken as hyperplastic polyps or lymphoid follicles and not treated for this reason.…”
Section: Misinterpreting the Lesionmentioning
confidence: 99%
“…The macroscopic features of PCCRCs, and especially the potential role of flat precursors in the development of PCCRs, have been less studied 11. In particular, non-polypoid (flat or depressed) adenomas can be more easily overlooked in routine practice,12 are more challenging to resect13 and a subset of them have the potential to progress more rapidly to cancer 14. A study by Farrar et al 15 conducted in a veteran population showed that PCCRCs are smaller in size and more often proximally located than prevalent CRCs, albeit the macroscopic appearance and aetiology of these cancers was not addressed in their study.…”
Section: Introductionmentioning
confidence: 99%